(untitled) (Jurnal Ilmiah Psikologi MIND SET, 2025)
Currently, Generation Y, the majority of employees in the company, is making a career change. Meanwhile, employees must have career commitment because it can raise awareness of the benefits of development for their career. Career commitment is influenced by job satisfaction, especially salary, training opportunities, career development opportunities, promotion, and interpersonal relationships, such as support from supervisors and coworkers. People committed to their careers also have good psychological capital because they believe in their abilities and are optimistic about their development. Based on this research, the purpose of this study is to find out the influence of job satisfaction and psychological capital on the career commitment of Generation Y. The sample in this study is the full-time employees who were born in 1980 until 2000 and have at least one year of working experience. This research using regression analysis. The result showed that job satisfaction had a significant influence on career commitment, and psychological capital had a significant influence on career commitment. Both, job satisfaction and psychological capital, had a significant influence on career commitment.